2017
DOI: 10.15419/bmrat.v4i11.383
|View full text |Cite
|
Sign up to set email alerts
|

Concise review: Medicinal plants are effective against leishmaniasis

Abstract: Leishmaniasis is an important zoonotic parasitic disease in tropical areas. It is a neglected disease and is a great health catastrophe in Iran. Pentavalent antimony compounds are used for its treatment, but they have adverse effects. Therefore, the use of natural herbs with low adverse effects seems necessary for treatment of Leishmaniasis. In this study, we tried to introduce the natural medicines effective against Leishmaniasis. In this review study, keywords searched included natural medicines, herbal medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In fact, during the last decade, natural compounds and their derivatives have been identified as a source of therapeutic agents. It was found that medicinal plants were effective against leishmaniasis [77]. The antileishmanial activities, on Leishmania infantum promastigotes, of 12 semisynthetic terpenoid derivatives obtained by several chemical modifications of E. resinifera major compounds (Demnat, Morocco) were studied by Mazoir et al (2011) [20].…”
Section: Antileishmanial Activitymentioning
confidence: 99%
“…In fact, during the last decade, natural compounds and their derivatives have been identified as a source of therapeutic agents. It was found that medicinal plants were effective against leishmaniasis [77]. The antileishmanial activities, on Leishmania infantum promastigotes, of 12 semisynthetic terpenoid derivatives obtained by several chemical modifications of E. resinifera major compounds (Demnat, Morocco) were studied by Mazoir et al (2011) [20].…”
Section: Antileishmanial Activitymentioning
confidence: 99%
“…102 Emetine and cephaline has potential for production of potent drugs against Leishmaniasis. 103 Emetine an anti-protozoal agent, potently inhibits both ZIKV and EBOV entry in vitro and potent activity in vivo. Cephaeline, a desmethyl analog of emetine, also displays a similar efficacy against ZIKV as well as EBOV infections.…”
Section: Biological Activities Of Emetine and Cephalinementioning
confidence: 99%
“…In recent years, the in vitro and in vivo anti-leishmanial activities of several plants, e.g. Pistachio species, Ziziphus spina-christi, Myrtus communis, Trichodesma africana and Pergularia tomentosa have been reported, which show that the use of these plants can lead to wound healing in animal models (Bahmani et al, 2015;Bahmani et al, 2017); however, final acceptance of the use of medicinal herbs for CL treatment is still held up by variable results of investigations that are seldom sufficiently powered.…”
Section: Introductionmentioning
confidence: 99%